'Bumping along': a qualitative metasynthesis of challenges to interprofessional placements. Issue 9 (10th May 2019) - O'Leary, Noreen; Salmon, Nancy; Clifford, Amanda; O'Donoghue, Michelle; Reeves, Scott
Abstract : Context: Interprofessional practice is required to manage complex health care needs globally. It is well established that interprofessional placements (IPP) prepare students to work collaboratively, yet IPP implementation remains limited and disjointed. Objectives: This review synthesised student, educator and service user perspectives in order to better understand challenges of IPP and provide recommendations for sustainable IPP implementation. Methods: A systematic metasynthesis of qualitative literature sourced from databases including CINAHL, Embase and PsycINFO was completed. Studies that incorporated student, educator and/or service user perspectives on IPP experiences were included. We focused specifically on factors limiting implementation of IPP. The presage‐process‐product (3P) theory provided the theoretical framework for inductive synthesis of 41 empirical studies. A confidence rating for findings was formulated using CERQual (confidence in evidence from reviews of qualitative research). Results: We developed three themes, which represent key challenges to IPP becoming embedded in placement culture: (i) thin theoretical foundations underpinned IPP, limiting understanding of the learning processes involved; (ii) implementation relied heavily on individual champions, which curtails investment and sustainability when personnel change, and (iii) students, educators and service users were unsure of the function of IPP and their respective roles, leading to uncertainty along with some negative perceptions of this placement approach. Conclusions: In line with the 3P theoretical framework, IPP would benefit from explicit connections with educational and change management theories during presage stage IPP requires coordinated leadership and resource investment, and during product stage clear integration of interprofessional learning outcomes in curricula is advised. Addressing the identified challenges across the stages of IPP will support further development of IPP, firmly establishing this approach within placement culture. IPP can them make a significant contribution to the development of a collaborative practice‐ready workforce. This in turn will enhance service user outcomes and safety. Abstract : This review provides an overview of the challenges faced during interprofessional placements and makes recommendations for facilitating collaborative practice to address increasingly complex healthcare needs.